The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/11562214_61
|View full text |Cite
|
Sign up to set email alerts
|

CTEMP: A Chinese Temporal Parser for Extracting and Normalizing Temporal Information

Abstract: Abstract. Temporal information is useful in many NLP applications, such as information extraction, question answering and summarization. In this paper, we present a temporal parser for extracting and normalizing temporal expressions from Chinese texts. An integrated temporal framework is proposed, which includes basic temporal concepts and the classification of temporal expressions. The identification of temporal expressions is fulfilled by powerful chart-parsing based on grammar rules and constraint rules. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Chinese: CTemp [6] is well known temporal expression extraction and normalization system for Chinese, which is based on temporal grammar rules.…”
Section: Related Workmentioning
confidence: 99%
“…Chinese: CTemp [6] is well known temporal expression extraction and normalization system for Chinese, which is based on temporal grammar rules.…”
Section: Related Workmentioning
confidence: 99%
“…As defined in [4], Chinese temporal expression can be classified as precise temporal expressions, fuzzy temporal expressions, modified temporal expressions, set-denoting temporal expressions, non-specific temporal expressions and so on. In [10], temporal parser for extracting and normalizing temporal expressions from Chinese texts is presented, the author also propose a temporal framework, which include basic temporal objects and relations, the measurement and classification of temporal expressions. For the purpose of inferring temporal information from multiple-clause sentences, a computational model based on machine learning and heterogeneous collaborative bootstrapping is build in [11] and the effects of linguistic features such as tense/aspect, temporal connectives, and discourse structures are also considered.…”
Section: Related Workmentioning
confidence: 99%
“…According to the TimeML standard, a label needs to contain four attributes: (1) tid, the index of temporal information in the record; (2) Type, the temporal type; (3) Value, the normalized date of a TE; and (4) anchorTimeID, the index of the reference time of the current TE. Each TE has a unique tag (eg, <TIMEX3 tid="t1" Type="TIME" Value="2014-10-11T07:48:16">2014/10/11 7:48:16</TIMEX3>, <TIMEX3 tid="t7" Type="DATE" Value="2014-08-02" anchorTimeID="t2">1 周前</TIMEX3>, <TIMEX3 tid="t4" Type="DURATION" Value="P1Y"> 1年 余</TIMEX3>, <TIMEX3 tid="t13" Type="SET" Value=" [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]" anchorTimeID="t11"> 第7、9、14 天 </TIMEX3>). These 900 EMRs contain 12,096 TEs (13.44…”
Section: Datasetsmentioning
confidence: 99%
“…Meanwhile, research related to Chinese TE extraction and normalization was reported. Wu et al [26] proposed a temporal parser to extract and standardize Chinese TEs. Zhou et al [27] established a framework concentrating on processing narrative clinical records in Chinese, including a regular expression matching-based method for TE identification and an approach for temporal relationship extraction using CRF.…”
Section: Introductionmentioning
confidence: 99%